Krisis Komunikasi dan Manajemen Reputasi: Pelajaran dari Kasus Kontroversi Kebijakan Publik di Indonesia - Maal Abrar; Ahmad Saudi; A’ang Chaarnaillan; Andi Kardian Riva’i; Hanifahturahmi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze the role of reputation management in addressing communication crises related to public policy in Indonesia, focusing on the case of the removal of fuel subsidies in 2022. The methodology employed is a qualitative approach using library research techniques, which involve the collection and analysis of relevant literature, including academic journals, government reports, and other publications on communication crises and reputation management. The findings indicate that ineffective and non-transparent communication from the government has led to confusion and dissatisfaction among the public. The response to this policy varied, with numerous protests and criticism from the media. In light of this situation, the government eventually adopted more transparent communication tactics through press conferences and the use of social media, which proved to have a positive impact on improving public image. Actively listening to public feedback through digital platforms also contributed to an increase in public trust towards the government. The lessons learned from this case highlight the importance of proactive early communication and public involvement in the decision-making process, as well as effective social media strategies for enhancing the government's reputation